A porous cellulose-based molecular imprinted polymer for specific recognition and enrichment of resveratrol. (1st January 2021) - Cao, Jingsong; Shen, Chen; Wang, Xiqing; Zhu, Yawei; Bao, Sansan; Wu, Xiaodan; Fu, Yujie
Highlights: Modified porous cellulose microspheres (p-CM@MPS) were prepared successfully. A Res molecularly imprinted polymer was prepared using p-CM@MPS as the carrier. The p-CM@MPS@MIP-Res showed remarkable adsorption capacity and reusability. The p-CM@MPS@MIP-Res was used as an adsorbent for resveratrol enrichment. Abstract: A novel resveratrol molecularly imprinted polymer (p-CM@MPS@MIP-Res) was prepared on the surface of silanized porous cellulose microspheres (p-CM@MPS) for the first time, and was successfully applied for the efficient enrichment of targeted resveratrol in Polygonum cuspidatum. The adsorption kinetics and adsorption equilibrium of p-CM@MPS@MIP-Res were also studied in detail. Compared with non-molecularly imprinted polymer (p-CM@MPS@NIP), the prepared p-CM@MPS@MIP-Res showed high adsorption capacity for resveratrol, the adsorption capacity of the p-CM@MPS@MIP-Res could reach to 11.56 mg/g. Furthermore, the stability of the p-CM@MPS@MIP-Res was evaluated and the result showed that the p-CM@MPS@MIP-Res could be reused for 5 runs. Finally, the p-CM@MPS@MIP-Res was applied to enrich the resveratrol in Polygonum cuspidatum sample, the content of resveratrol in the extraction solution could be increased greatly from 4.23 % to 23.74 %, indicating the p-CM@MPS@MIP-Res was a promising adsorbent for efficiently separation and enrichment of resveratrol in Polygonum cuspidatum.